Gambaran Indeks Volum Atrium Kiri pada Disfungsi Diastolik - Herawati Isnanijah; Ameliana M Soetanto; Muhammad Munawar (The Indonesian Heart Association, 2007)
Background. Diastolic dysfunction is frequently found in hypertension,usually accompanied with left ventricular hypertrophy. Several parameter was developed to assess the diastolic function including left atrial volume index, E/A, DT, IVRT, S/D, E/e’, and e’/a’. There is no data of left atrial volume index for normal subjects or subjects with hypertensive heart disease in Indonesian population. The aim of this study is to prove that left atrial volume index can be used as a parameter for left ventricular diastolic dysfunction in hypertensive heart disease.Methods and results.Fifty hypertensive heart disease patients with normal left ventricular systolic function, who were hospitalized in NCCHK between January-October 2006, and had follow up at the outpatient clinic were examined. We evaluated the correlation between left atrial volume index and E/A ratio, S/D, E/e’, e’/a’. The left atrial volume index in normal subjects is 17.64 ± 1.35, in subjects with grade 1 diastolic dysfunction 23.26 ± 2.55, while in subjects with grade 2 diastolic dysfunction 31.35 ± 2.87. Value among those groups differ significantly with p = 0.001.Conclusions. There is significant difference of left atrial volume index among normal subjects, subjects with grade 1 and grade 2 diastolic dysfunction.